The complement system is activated in synovial fluid from subjects with knee injury and from patients with osteoarthritis - Struglics, André; Okroj, Marcin; Swärd, Per; Frobell, Richard; Saxne, Tore; Lohmander, L. Stefan; Blom, Anna M. (Arthritis research & therapy, 2016)
The complement system is suggested to be involved in the pathogenesis of osteoarthritis (OA), and proinflammatory cytokines may play a role in OA development by inducing proteases. The association between complement factors, cytokines and OA has not been investigated. The aim of the present study was to explore the involvement of the complement system after knee trauma and in OA. C4d, C3bBbP and soluble terminal complement complex (sTCC) resulting from complement activation were immunoassayed in synovial fluid from subjects with healthy knees (reference), OA, rheumatoid arthritis (RA; positive control), pyrophosphate arthritis (PPA; positive control) and knee injury; other biomarkers were previously assessed. Magnetic resonance imaging was used to assess joint injuries. Compared with levels in the reference group, the median concentrations of C4d, C3bBbP and sTCC in the OA, RA, PPA and knee injury groups were 2- to 34-fold increased (p < 0.001 to p = 0.044). For the knee injury group, the median concentrations of C4d, C3bBbP and sTCC were 5- to 12-fold increased (p < 0.001) at the day of injury; after 3-12 weeks, C3bBbP and sTCC concentrations were similar to reference levels; and C4d was still increased several years after injury. In the 0-12 weeks period after injury, the concentrations of C4d, C3bBbP and sTCC correlated positively with levels of interleukin (IL)-1β, IL-6 and tumour necrosis factor α (r range 0.232-0.547); none of the measured complement factors correlated with proteolytic fragments of aggrecan or cartilage oligomeric matrix protein. Knees with osteochondral fracture, with or without disrupted cortical bone, had higher concentrations of C4d (p = 0.014, p = 0.004) and sTCC (p = 0.004, p < 0.001) compared with knees without fractures. The complement system is activated in OA and after knee injury. Following knee injury, this activation is instant and associated with inflammation as well as with the presence of osteochondral fractures.